STUDI HUBUNGAN SURPLUS FREE CASH FLOW TERHADAP KECENDERUNGAN MELAKUKAN EARNINGS MANAGEMENT PADA BADAN USAHA SEKTOR MANUFAKTUR DI BEI PERIODE 2010-2011 - Cecilia Liony Surya; Stevanus Hadi Darmadji; Aurelia Carina Sutanto (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2013)
The purpose of this study is to examine the relationship between surplus freecash flow (SFCF) and earnings management. This study argues that managersin companies with low growth and high surplus free cash flow tend to usediscretionary accounting accrual (DAC) to offset negative earning related to their investments with negative net present value (NPV). Besides that, we expect that the positive relationship between surplus free cash flow (SFCF) and earnings management is moderated by audit quality and institutional shareholder. This research uses quantitative approach with 205 companies listed in Bursa Efek Indonesia for the year 2010 – 2011 as a sample. The findings of this research show that there is positive significant relationship between high SFCF in company that has low growth with earnings management. This study failed to proof that audit quality and institutional shareholder moderate the relationship between high SFCF and earnings management.